Germany : 2020 skills forecast - (:unkn) unknown (European Centre for the Development of Vocational Training, 2020)
The Cedefop Skills Forecast offers quantitative projections of future trends in employment, by sector of economic activity and occupational group. Future trends in the level of education of the population and the labour force are also estimated. Cedefop's forecast uses harmonised international data and a common methodological approach allowing cross-country comparisons between employment trends in sectors, occupations and qualifications. The forecast and methodology is validated by a group of national experts. The forecast does not substitute national forecasts, which often use more detailed methodologies and data, while they also incorporate in-depth knowledge of a country's labour market. The Cedefop Skills forecast was developed before the global Covid-19 pandemic had begun. The short-term economic impacts of the pandemic and subsequent lockdowns in many countries are very uncertain, and therefore the current short-term forecast is likely to be over-optimistic. However, the key long-term factors [...] will still hold as the EU Member States put plans in place to deal with the virus and their economies move forwards. The trends in the longer-term forecast are therefore still likely to hold. (excerpt; BIBB-Doku)
Keywords: G 1.2 Arbeitsmarkt; G 1.2.3 Qualifikationsentwicklungen; Arbeitsmarktentwicklung; Erwerbsbeteiligung; Qualifikationsstruktur; Prognose; 2018-2030